Tracking dietary habits of cave arthropods associated with deposits of hematophagous bat guano: A study from a neotropical savanna - Salgado, S.S.; Motta, P.C.; De Souza Aguiar, L.M.; Nardoto, G.B.
Carbon and nitrogen stable isotopes were used to track major dietary variations in arthropods found in a cave located in a neotropical savanna in Central Brazil. We determined the d13C and d15N for cave crickets, cockroaches, spiders, guano of a hematophagous bat, and leaf litter found on the ground near the cave entrance. The d13C and d15N for the cricket and cockroaches showed that bat guano was not the only food item for these arthropods. They had intermediate d13C and d15N between bat guano and leaf litter, which means that they consumed additional food resources other than guano in their diet, independent of distribution of guano deposits in the cave. The spiders, predators with great mobility, seemed to not have a preferential diet item since their isotope signals indicated they hunt both crickets and cockroaches. The d13C of the bat guano (-15.4%)indicated that the diet of these hematophagous bats relied on animals fed with C4 plants. The conversion of native savanna vegetation of which the debris is mostly from C3 plants, to pasture, based on C4 African grass, a remarkably common land use transformation in the region, is indirectly influencing the diet of hematophagous bats, which basically relied on exotic fauna. The C and N stable isotope ratios showed that the arthropods inside the cave do not rely solely on bat guano for their diet, but interact directly with the external environment, through litter debris, indicating a significant exchange of energy and matter between the cave environment and the surrounding area. © 2014 Ecological Society of Australia.
Keywords: ARTHROPOD; BAT; BIOENERGETICS; CAVE; CERRADO; DIET; FEEDING BEHAVIOR; FOOD CHAIN; FOOD PREFERENCE; GUANO; LEAF LITTER; NEOTROPICAL REGION; NITROGEN; SAVANNA; STABLE ISOTOPE